Effect of electron beam irradiation on the mechanical properties of buriti fiber - Barbosa,A. P. (2012)
Natural fibers, mainly those lignocellulosic extracted from plants, have, in the past few decades, attracted the attention not only of scientists but also of industrial technologists of our society interested in their engineering materials. As it is well known, uses of natural fiber in clothes carpets, baskets, ropes and low cost construction roofing has existed from the beginning of our civilization. Today environmental and energy saving issues are motivating research works on new uses of lignocellulosic fibers in polymer composites. Moreover, industrial application of lignocellulosic fiber composites are already in technological sectors such the automobile industry, packing and civil construction. In addition to environmental, economical and social benefits, some lignocellulosic fibers present specific properties that are not comparable to those of other synthetic fiber used for polymer composite reinforcement. In fact, the mechanical strength and stiffness of any natural fibers is, however, significantly inferior and needs to be improved in order to compete with those of the synthetic fibers. The present work investigated the effect of electron beam irradiation on the mechanical behavior of the buriti petiole fiber, which presents a potential for composite reinforcement. Distinct lots of buriti fibers were irradiated at 50, 250 and 500 kGy using a 1.5 MeV electron beam accelerator. The results showed marked changes in the tensile properties of the buriti petiole fiber. This was discussed in terms of the structural modifications occurring in the irradiated lignocellulosic structure.